El juego en el proceso de inclusión en los niños de Inicial 2 de la Escuela de Educación Básica “Augusto Nicolás Martínez” del cantón Píllaro - Camañero Moya, Amanda María (2024)
This main objective of this research study entitled "El juego en el proceso de inclusión de los niños de Inicial 2 de la Escuela de Educación Básica Augusto Nicolás Martínez" Primary School in Píllaro. An investigation about play and inclusion at an educational level, creating a guide that aims to develop playful strategies for educational inclusión that allows for significant learning through play, creating motor activities and equal opportunities among the students of the "Augusto Nicolás Martínez" Primary School. Games play an important role at an educational level, they are often planned and designed to address procedural content, mainly in primary schools as they are fun for children and generate learning. Not only is it an incredibly valuable tool for generating learning around the curriculum, but it is also an excellent tool for fostering inclusion. The methodological approach of this work is Quantitative of non-experimental design with a characteristic study, with a population of 12 boys and 13 girls with a total of 25 students, by the place is of field and bibliographic type; that allowed to establish the techniques of collection of information as it is the observation, the instrument is the guide of motor activities for the inclusion using the game, the same one that was applied to the children of Initial 2, of the school of basic education "Augusto Nicolas Martínez". It is concluded that through the socialization of the guide of motor activities, it was possible to promote inclusion through play using our instrument, achieving excellent acceptance, and raising awareness among both teachers and pupils.